Didactic Potential of Instructive Etude and its Explication in the Process of Professional Development of a Pianist - Ivanova, Iryna; Chernyavska, Marianna; Pupina, Olesia (Journal of History Culture and Art Research, 2020)
The article proposes an analytical approach to instructive etude as a musical work whose originality is determined by its functional orientation: not to demonstrate performing skills in mastering all its components or to embody author’s reflection, but to develop and improve students' practical skills. The creation of etude forming piano music in its sense in the aggregate of composing, performing, and teaching practices at their intersection allows us to see there a reflection of all the process facets stressing one of them. The instructive branch of the study, incorporating the finds of both performers and composers, projects them onto teaching materials, highlighting individual technical and textural techniques and turning them into the units of training work. The formation and improvement of the pianistic apparatus, the accuracy of touching the keyboard, free movement within its space boundaries, ease and fluency of fingers, etc., remain the most fundamental, basic task of instructional etude. However, the faultless technique and motility do not exhaust the content of the training work proposed by an etude’s author, but include other skills that also need careful work, including auditory control, the ability to withstand the taken tempo-rhythm, mastering various articulations, etc. The breadth and variety of methodological tasks posed in individual samples of instructive etudes are pointed out, which makes it possible to refer to them as a powerful aid in all stages of teaching music to students, including higher special musical institutions. Whether to use them in academic repertoire or abandon should depend only on a particular student’s professional level, and on his being ready to play compositions of increased difficulty, including artistic etudes. The conclusion is made about didactic potential steadiness inherited in this type of works and the tendency to explicate it in a pianist’s professional development process.